2018
DOI: 10.1186/s12887-018-1051-9
|View full text |Cite
|
Sign up to set email alerts
|

A pediatric death audit in a large referral hospital in Malawi

Abstract: BackgroundDeath audits have been used to describe pediatric mortality in under-resourced settings, where record keeping is often a challenge. This information provides the cornerstone for the foundation of quality improvement initiatives. Malawi, located in sub-Saharan Africa, currently has an Under-5 mortality rate of 64/1000. Kamuzu Central Hospital, in the capital city Lilongwe, is a busy government referral hospital, which admits up to 3000 children per month. A study published in 2013 reported mortality r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 29 publications
0
29
0
2
Order By: Relevance
“…Hence these patients are different from patients with other deadly infectious diseases, e.g. malaria, cholera, leishmaniasis, where patients have no other choice but to report early and follow medical instructions [ 50 , 51 ]. Moreover, mycetoma patients with early lesions differ from patients with large disabling mycetoma lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Hence these patients are different from patients with other deadly infectious diseases, e.g. malaria, cholera, leishmaniasis, where patients have no other choice but to report early and follow medical instructions [ 50 , 51 ]. Moreover, mycetoma patients with early lesions differ from patients with large disabling mycetoma lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Even in an era of ‘big-data’ 27 28 learning the lessons from detailed analysis of individual cases has an important value. 7 WHO held a meeting on Child Death Review in Geneva in November 2016, and this study was an attempt to pilot the tools developed and evaluate the process.…”
Section: Discussionmentioning
confidence: 99%
“…A rudimentary root cause analysis for each death was postulated, and subsequent recommendations were made. It was observed informally by the researcher-in-residence (CC) that the quality of the paper records is very poor [ 12 ], with faded, illegible writing, and the death audit process is time-consuming and often takes a whole day. She also observed that clinicians find it particularly difficult to attend death audits as their clinical duties continue.…”
Section: Methodsmentioning
confidence: 99%
“…Despite being one of the least developed countries in the world, Malawi has seen great success in achieving the Millennium Development Goal 4 [ 11 ], particularly for underfive mortality; however, for newborns, mortality is persistently high. A previous pediatric death audit in Kamuzu Central Hospital (KCH), a large referral center in Malawi, was recently published and cited reliable records as a significant limitation, with 6% of charts missing and documentation deficiencies in 58% of the charts reviewed [ 12 ]. To our knowledge, a perinatal death audit has not yet been published from Malawi or other sub-Saharan countries.…”
Section: Introductionmentioning
confidence: 99%